DEGREES OF SEPARATION: HILLSLOPE-CHANNEL COUPLING AND THE LIMITS OF PALAEOHYDROLOGICAL RECONSTRUCTION - Wainwright J. (My University, 2006)
Qualitative analysis of hillslope-channel coupling conditions suggests that the internal configuration of a catchment has a strong influence on the transfer of water and sediment through the fluvial system. Consequently, similar climatic inputs into catchments with otherwise similar characteristics can result in very divergent responses. A cellular modelling approach has been used to evaluate the potential magnitude of this effect, and to investigate the implications for palaeohydrological investigations. Simple catchments with coupled and progressively uncoupled conditions (marked by the presence of one and two floodplain levels) were subjected to simulated climate change using a 740 ka proxy climate record. Dynamic flow and sediment routing were simulated, and vegetation and soils allowed to evolve in parallel. The results suggest that catchment configuration has a very strong effect producing a complex system response based on the output of sediment from the catchment and that there are no simple relationships between climate and catchment output. The complex response itself also evolves through time as the catchment dynamically reorganizes, implying that system trajectory and historical contingency are also significant factors. Although events may be captured in the sedimentary record, these events will often relate to pulses of sediment working their way through the system, rather than being directly related to climate changes or variability. The complex, non-equilibrium behaviour of the system suggests that climate proxies derived from even high-resolution palaeohydrological records should be treated with extreme caution.
Keywords: Catchment hydrology; Climate proxies; Geomorphic modelling; Complex response; Landform evolution; Equifinality; Divergence